2012
DOI: 10.4103/0971-4065.98758
|View full text |Cite
|
Sign up to set email alerts
|

Effect of reuse of polysulfone membrane on oxidative stress during hemodialysis

Abstract: Patients with chronic renal failure, especially those on long-term hemodialysis (HD), have a high incidence of premature cardiovascular disease. Oxidative stress, which occurs when there is an excessive free radical production or low antioxidant level, has recently been implicated as a causative factor in atherogenesis. Hourly changes in malondialdehyde (MDA) and antioxidant enzymes, vitamins, lipid profile and ferric reducing ability of plasma (FRAP) were studied with the first use and immediate subsequent re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Both studies demonstrated no significant difference in CAT activity at the end of the dialysis session, which supports the results of this study. Ramakrishna et al [4] and Wu et al [24] also observed that GPx activity did not change after the dialysis session. By contrast, researchers have shown a reduction in SOD activity after a session of dialysis [25,26] .…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Both studies demonstrated no significant difference in CAT activity at the end of the dialysis session, which supports the results of this study. Ramakrishna et al [4] and Wu et al [24] also observed that GPx activity did not change after the dialysis session. By contrast, researchers have shown a reduction in SOD activity after a session of dialysis [25,26] .…”
Section: Discussionmentioning
confidence: 94%
“…The data regarding the plasma CAT and GPx levels after the dialysis session are controversial. Some studies have reported an increase [4,5] , whereas others have reported no alteration [4,22–24] or even a decrease after a HD session [25–27] . In this study, we observed no significant differences in these enzymes 1 hour after initiating the dialysis session.…”
Section: Discussionmentioning
confidence: 98%
“…Taking into consideration of the clearance of MDA during dialysis, the ratio of MDA and creatinine was likely to give a better picture about MDA during dialysis. After correcting MDA for creatinine, we found a significant increase in MDA levels from pre-dialysis to the post-dialysis indicating that the increase in MDA during HD was due to its increased production consequent to oxidative stress, rather than getting cleared by dialysis [ 26 ]. This increase in post-HD MDA was an indicator of the presence of oxidative stress during the dialysis session [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Compared to non-reused LF membranes, reused ones were associated with improved survival, while reusing HF dialyzers had essentially no impact on survival. As dialyzer reuse [ 70 ] is generally [ 71 – 73 ], but not invariably [ 74 76 ] associated with enhanced biocompatibility and reduced oxidative stress, it would be tempting to speculate that this discrepancy can be attributed to an improvement in biocompatibility seen only with reuse of LF dialyzers. However, a selective increase in the biocompatibility of LF dialyzers by reuse appears unlikely for a number of reasons.…”
Section: Discussionmentioning
confidence: 99%
“…To the extent that HF dialyzer reuse is a necessary component of a dialysis program for environmental [ 57 ], financial (e.g. other dialysis providers in the USA) [ 88 ] or resource constraint (as in lower income countries) [ 14 , 76 , 89 , 90 ] reasons, we believe that reused HF dialyzers may realize the same benefits over non-reused LF dialyzers and thus HF membranes should also be preferred. Though extensive reuse of LF dialyzers is unlikely to ever be practiced except in severely resource-constrained settings, our re-exploration of HEMO suggests that there may be upsides in not adopting HF dialysis in these environments.…”
Section: Discussionmentioning
confidence: 99%